1994
DOI: 10.1007/bf00203295
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and the dynamics of displacive phase transitions in cryolite (Na3AlF6) and chiolite (Na5Al3F14): Multi-nuclear NMR studies

Abstract: Abstract.Cryolite is a mixed-cation perovskite (Na2(NaA1)F6) which undergoes a monoclinic to orthorhombic displacive phase transition at ~ 550 ~ C. Chiolite (NasA13F14) is associated with cryolite in natural deposits, and consists of sheets of corner sharing [A1F6] octahedra interlayered with edge-sharing [NaF6] octahedra. Multi-nuclear NMR line shape and relaxation time (T1) studies were performed on cryolite and chiolite in order to gain a better understanding of the atomic motions associated with the phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
45
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 41 publications
8
45
0
3
Order By: Relevance
“…Results from NMR spectroscopy indicate an increased ionic mobility already above T = 100 • C, well within the stability range of the monoclinic phase [6,7]. The observed changes in the chemical shift and the merging of the two peaks from the differently coordinated Na ions are interpreted as rapid cation exchange between the Na V I and Na V III sites.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…Results from NMR spectroscopy indicate an increased ionic mobility already above T = 100 • C, well within the stability range of the monoclinic phase [6,7]. The observed changes in the chemical shift and the merging of the two peaks from the differently coordinated Na ions are interpreted as rapid cation exchange between the Na V I and Na V III sites.…”
Section: Introductionmentioning
confidence: 72%
“…Diffusion rates may be obtained from NMR data [2,6,7], but the sensitivity of NMR is usually limited to jump frequencies up to the kHz range. For faster ionic mobility, experimental data are rare due to experimental difficulties of performing in situ experiments at high T where fluoride samples often become very reactive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At low temperatures, far below the first transition, NMR studies confirmed Na + exchange between the six and eight fold coordinated site in the kHz frequency range [10,11]. At T = 880 K, which is in the stability field of the cubic phase, the two sites are indistinguishable on the time scale of NMR.…”
Section: Introductionmentioning
confidence: 88%
“…Posee una estructura de tipo perowskita, de gran actualidad tanto desde el punto de vista geológico como para la ciencia de los materiales. Además exhibe una conducta muy especial, con transiciones de fase y movilizaciones ató-micas asociadas a ellas, que son responsables de sus peculiares propiedades mecánicas y eléctricas (2). Por encima de los 450ºC se comporta como un flujo plástico que podría ser la explicación de las brechas del yacimiento de Ivigtut (Groenlandia), donde criolita pura constituye el cemento de los clastos de la roca (Ivigtut ha sido el depósito industrial mas grande del mundo, en la actualidad prácticamente agotado) (3).…”
Section: Introductionunclassified